Immune Responses of Club Cells in Fish: A Review - Dhamayanti, Yeni; Khairunnisa, Hanifa Khansa; Zahrudin, Elham; Bayram, Muhammet; Suciyono, Suciyono (Jurnal Medik Veteriner, 2024)
The primary line of defense against pathogens from the environment is often fish epidermis tissue. Nevertheless, little is understood about the physiological mechanisms that underlie the non-specific and/or specific protection that these cells can offer. The exact nature of the relationship between the evolution of ostariophysan fish club cells and chemical warning signals is still unknown and controversial. Fish epidermis layer cells comprise mucus cells, lymphocytes, macrophage cells, cuboidal and squamous epithelial cells, and cells specific to certain fish species. Club cells, also called "alarm cells," are chemical alarms that sound in the event of a potentially hazardous scenario. These cells will burst in the presence of a predator, releasing pheromones that, if the skin is physically damaged, trigger an avoidance and terror reaction. In sturgeon larvae, mucus cells were visible in week 1, but club cells did not appear until week 4. Due to their later development during ontogenesis and after wounding, club cells may not have as much of a protective effect during wound healing as filament or mucus cells. Club cells are mostly found in the epidermis of the skin, and it is thought that when they work in tandem with mucus and goblet cells to fight infections, they serve as the body's first line of defense.